Photovoice as a narrative tool for decolonization: Black women and LGBT student experiences at UCT - Kessi, S. (South African Journal of Higher Education, 2018)
Decolonization is a key term in the current higher education crisis across South African universities as student movements are advocating for free decolonized education. In this paper, I explore how Photovoice research, as a narrative approach combined with participatory action methods, can engage a group of black, working-class, and LGBT students at the University of Cape Town (UCT) to explore their daily experiences on campus in relation to the call for decolonization. Findings demonstrate how naming decolonization allows students to locate their own experiences within a context of power relations and expose alienating institutional legacies. Of particular relevance are the experiences of students of diverse gendered identities whose daily struggles are often rendered invisible through multiple bureaucratic and cultural assumptions. Students spoke about the violence of institutional spaces, the policing of their bodies and the silencing of alternative ways of knowing and doing.